The influence of the technology-organization-environment framework and strategic orientation on cloud computing use, enterprise mobility, and performance - Picoto, Winnie Ng (2021)
Purpose – The objective of this paper is threefold. It aims i) to identify the antecedents of the use of cloud computing, ii) to understand the effect of the use of cloud computing together with strategic orientations on enterprise mobility, and iii) to comprehend the effect of the use of cloud computing and enterprise mobility on organizational performance.Theoretical framework – This paper builds on the technology-organization-environment framework and on previous studies of enterprise mobility to propose a comprehensive research model to analyze cloud computing adoption and usage. In addition, the strategic orientation framework is applied as support for a reorientation of strategy toward enterprise mobility.Design/methodology/approach – We developed a questionnaire and collected data from 137 Portuguese organizations that are using cloud computing. The data collected were then analyzed through partial least squares (PLS-SEM).Findings –The results indicate that convenience, compatibility, and organizational confidence are significant antecedents of the use of cloud computing. Moreover, cloud computing usage, innovation orientation, and entrepreneurial orientation have a positive effect on enterprise mobility.Research Practical & Social implications – This study contributes to this field of research, since it contains the first research model to integrate cloud computing usage, enterprise mobility and strategic orientation, confirming the relationship between those constructs. As practical implications, the results show that greater usage of both cloud computing and organizational mobility is important to achieve superior levels of organizational performance.Originality/value – This paper proposes an integrative model to analyze the use of cloud computing by organizations, in terms of its antecedents and impacts on firm performance and enterprise mobility.